URGENSI PENGATURAN KETAMIN DALAM UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Risqi, Dimas Moch.; Yudianto, Otto (Mimbar Keadilan, 2022)
This study aims to explain the urgency of regulating ketamine in Law Number 35 of 2009 concerning Narcotics. This research method uses normative juridical and this research is perspective to answer the problem formulation on legal issues so that it can provide opinions and views on legal issues that are studied. The approach method used is the Legislative Approach (Statute Approach) and Conceptual Approach. The results obtained from a juridical point of view are that perpetrators who abuse ketamine in this case distributing ketamine are only charged with Law Number 36 of 2009 concerning Health. Perpetrators of ketamine abuse cannot be charged with Law Number 35 of 2009 concerning Narcotics because the Act does not regulate ketamine as a type of narcotic. So that following with the Legality Principle of criminal law Article 1 Number 1 of Law Number 1 of 1946 concerning Criminal Law Regulations explains that an act cannot be threatened with criminal punishment if there is no criminal regulation that regulates it beforehand. From a sociological perspective, the side effects of ketamine are very dangerous, they can affect a person's condition in society. Ketamine which has the same effect as narcotics in general makes people feel that this ketamine must be taken into account in the laws and regulations so that perpetrators who abuse ketamine can be punished so that it has a deterrent effect.